Influência do tipo de meio suporte no desempenho de biofitros aplicados à remoção de H2S do ar atmosférico em sistemas de esgoto sanitário - Silva, Marjorye Boldrini da (2008)
The odor emissions affect the quality of life, promoting psychological stress through symptoms such as sleeplessness, appetite loss and change of behavior. Odors emitted in Wastewater Treatment Plants (WWTP) are produced by the biological degradation of the constituents of domestic sewer, due to anaerobic activity. Amongst the produced composites are distinguished the sulfidric gas, that is very used as an indicator. The H2S is a gas that presents a long list of inconveniences: it is toxic, bad-odorant (rotten egg odor) and is extremely corrosive in humid atmosphere. There exists many options of odor treatment; amongst them the biofiltration reveals as a cheap and simple technology. Due to such fact, this research proposes a study of the composition of bio-filters treating the atmosphere of a pumping station and the evaluation of the emission rate of H2S observed and estimated by mathematical model. The main goal was to compare different natural materials for the filter bed, and to evaluate the efficiency of removal of the H2S obtained by the bio-filters. The materials used in the filling were: soil, sugar cane bagasse and coffee straw + dewatered anaerobic sludge. The research was divided in four stages: the first one without humidification column, and the II, III, and IV with humidification column filled with water with pH 9,0. The evaluated operational conditions were: Stage I (Cv=1,07g/m3 .d and Tr=37,7s); Stage II (Cv=1,2g/m3 .d and Tr=37,7s); Stage III (Cv=0,73g/m3 .d and Tr=25,12s) and Stage IV (Cv=4,04g/m3 .d and Tr=12,56s). The study of the emission rate observed was made with the flow chamber methodology and the average value found was 0,6mg/m2 .h, the modeling was made with the GPC and was found a relative error equal to 387%. The removal efficiencies found in the stages were, respectively, for the bio-filter of soil, sugar cane and coffee: Stage I = 91, 73 e 66%; Stage II = 88, 79 e 90%; Stage III =89, 91 e 91% e Stage IV = 74, 71 and 88%. The characterization of the materials showed that, in terms of porosity, presence of nutrients and humidity, the materials are proper for the proposed kind of use. The smaller efficiency obtained in the first stage is caused by the absence of the humidification columns, occurring the drying of the materials inside the bio-filter. After analysis of the concentration of H2S before and after the passage of air inside these columns, it was verified that there was no removal of the pollutant in this passage of the air flow.